Text to Color Image Steganography Using LSB Technique and XOR Operations - Devi Ratnasari; Adam Sekti Aji (International Journal of Applied Business and Information Systems, 2019)
Steganography technique is the art of hiding information in the carrier media to prevent humans from detecting messages or confidential information inside the carrier media. Nowadays steganography has become one of the solutions for information security and confidentiality. This paper applies steganography to hide the text messages into digital color images based on the RGB color model which is also used as a non-secret message. There are two proposed schemes namely the embedding scheme and the extraction scheme by applying the LSB (Least Significant Bit) and triple XOR operation techniques to the binary value of MSB (Most Significant Bit). In addition, a statistical analysis was carried out to measure the quality and difference between the cover image and stego-image by calculating the MSE (Mean Square Error) and PSNR (Peak Signal to Noise Ratio) values.